Peningkatan Kompetensi Menulis Buku Ajar: Upaya mewujudkan Pembelajaran Orisinal Melalui Pelatihan Online di Universitas Teknologi Sumbawa - Hakim, Lukmanul; Junadin, Junadin; Yanuar, Emsal; Ananda, Nova Adhitya (Jurnal Gema Ngabdi, 2024)
Quality learning is strongly supported by the availability of textbooks. Through the work produced by lecturers in the form of textbooks, it will have an impact on the originality of learning. This activity aims to improve the competence of lecturers in writing textbooks through online training. The implementation of the activity by the Academic Directorate of the Innovation Center (PIA) of the University of Technology using the Zoom platform. The delivery method uses lectures and responses. Participants totaled 47 people from representatives from 6 faculties. The results of the activity showed that participants were involved in providing responses to questions and responses, understanding the content of the material, and participants' readiness in writing textbooks. The results of the evaluation were carried out through a pre-test with a score of 60% and a post-test of 93% with an increase of 33% N-Gen. This activity is a good effort to improve the competence of writing textbooks as part of realizing original learning.